Characterization of genetic variation in secondary metabolites in Fusarium - Yue, Wei (Kansas State University, 2017)
Secondary metabolites (SMs), low molecular weight molecules that are not essential for normal organism growth and development, may confer a selective advantage in some environments. Fungal SMs are structurally and functionally diverse and include mycotoxins, plant regulators and pigments, and the genes that work together in SM biosynthetic pathways are physically clustered in the genome. Fusarium, a genus of filamentous fungi, is noted for SM production, especially mycotoxins, which may contribute to plant pathogenesis. Fusarium species exhibit differences in their SM profiles, and comparative genomics studies have found corresponding differences in the SM gene clusters in some Fusarium species. The investigation of differences in the genomes and SM gene clusters between closely related species, such as F. proliferatum and F. fujikuroi, may help explain their phenotypic divergence, including differences in SM profiles. In addition, the study of intra-species SM variation may indicate how SM loci affect a pathogen’s fitness traits. My research includes three main projects that address different aspects of Fusarium SM variability. To carry out my projects, I established a feasible Genotyping-by-Sequencing (GBS) protocol for Fusarium. One project explored the genetic bases underlying phenotypic divergence related to SM profiles and pathogenicity between F. proliferatum and F. fujikuroi using a quantitative genetics approach. Specifically, I 1) constructed the first high density genetic map based on progeny from an interspecific cross between these two species; and 2) detected a novel regulatory locus for gibberellic acid production and identified a region affecting onion virulence that includes the fumonisin gene cluster. The second project characterized the F. proliferatum parent genome from the previous cross and its SM gene clusters using a comparative genomics approach. Specifically, I 1) assembled the F. proliferatum genome into 12 chromosomes with a combined length of ~43 Mb; 2) annotated this assembly and characterized its 50 SM gene clusters; and 3) detected over 100 F. proliferatum specific genes that might play roles in this species’ host specificity and plant pathogenicity. The third project used a population genomics approach to explore how different F. graminearum chemotypes, or isolates classified based on the accumulation of alternate trichothecene toxin types, may differ for fitness traits and whether trichothecene genes are directly responsible for these differences. Specifically, I 1) genotyped over 300 F. graminearum strains from New York and the upper Midwest in the U.S. and from South America using our GBS protocol; 2) detected two major subpopulations that were correlated, though imperfectly, to the predicted 3-acetyl deoxynivalenol (3ADON) and 15-acetyl deoxynivalenol (15ADON) chemotypes in the U.S.; 3) identified a rapid linkage disequilibrium decay over a few tens of kb followed by a slower decay to background levels over a distance of 200 kb to 400 kb in selected subpopulations in the U.S.; and 4) found that neither chemotype has a clear fitness advantage in a small set of isolates from New York, but that isolates belonging to one genetic subpopulation may on average have a fitness advantage over isolates from the other subpopulation.
Keywords: Secondary metabolite; Genetics; GenomicsFusarium